Speech recognition - 207859 Mohammad Masroor Ahmed; Abdul Manan Ahmad; International Conference on Computer Graphics and Multimedia (2nd : 2004 : Bangi, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
16